2008
DOI: 10.1111/j.1365-2966.2008.13426.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-fluid models of superfluid neutron star cores

Abstract: Both relativistic and non-relativistic two-fluid models of neutron star cores are constructed, using the constrained variational formalism developed by Brandon Carter and co-workers. We consider a mixture of superfluid neutrons and superconducting protons at zero temperature, taking into account mutual entrainment effects. Leptons, which affect the interior composition of the neutron star and contribute to the pressure, are also included. We provide the analytic expression of the Lagrangian density of the syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 63 publications
(112 reference statements)
1
97
0
Order By: Relevance
“…Temperature evolution is chosen as given by equation (15). Microscopic parameters related to effective masses are taken from Chamel (2008). The toroidal field is considered to reach its maximum intensity at a region with R = 0.8R * .…”
Section: Results For Radio Pulsarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature evolution is chosen as given by equation (15). Microscopic parameters related to effective masses are taken from Chamel (2008). The toroidal field is considered to reach its maximum intensity at a region with R = 0.8R * .…”
Section: Results For Radio Pulsarsmentioning
confidence: 99%
“…Since m * p /mp < 1, proton mass current is inversely directed with the neutron velocity field. Chamel (2008) has shown that effective to bare mass ratio for Douchin & Haensel (2001) and Akmal et al (1998) equations of state changes in the range m * p /mp ≈ 0.9 − 0.4 throughout the entire core depending upon the nucleon-nucleon interactions which in turn depends on the density.…”
Section: Application To the Post-glitch Relaxations Of The Radio Pulsmentioning
confidence: 99%
“…a radius in the range of 11.5 ± 1.2 km. Fortunately, the SLy4 equation of state [34,42] satisfies these criteria. This model also suits our purposes by involving the simplest reasonable composition.…”
Section: Key Aspects Of the Modelmentioning
confidence: 99%
“…To model the star's core, we use the numerical fit to the SLy4 EoS proposed by Chamel [34,42]. This is a zero temperature EoS which accounts for the presence of a mixture of superfluid neutrons and superconducting protons in the core, and includes the entrainment effect.…”
Section: A the Background Configurationmentioning
confidence: 99%
See 1 more Smart Citation